Effects of cyclosporin, nifedipine and phenytoin on gingival myofibroblast transdifferentiation in monkeys - Kanno, Claudia Misue [UNESP] (2019)
Objective: Myofibroblasts have been associated with the development of several pathologic fibrotic conditions. This longitudinal study aims to assess the proliferative and antiapoptotic effects of cyclosporin, nifedipine and phenytoin on gingival connective tissue cells of nonhuman primate, as well as to analyze a possible role of myofibroblasts in gingival overgrowth. Materials and Methods: Gingival samples from the right superior canine area were obtained from 12 male monkeys (Sapajus spp) to comprise the control group. After one week, the animals were randomly assigned to three groups, which received daily oral doses of cyclosporin, nifedipine or phenytoin for 120 days. Gingival samples were collected from the left superior canine area of two animals of each group at 52 and 120 days. Histological sections were stained with hematoxylin and eosin, and immunoreacted against alpha-SMA, Ki67 and bcl-2. Results: alpha-SMA immunoreaction was negative in the control and experimental groups. Similarly, no difference between groups concerning immunostaining against Ki-67 and bcl-2 was observed in connective tissue cells. Conclusion: Based on this methodology, it may be concluded that gingival overgrowths induced by cyclosporin, nifedipine and phenytoin are not associated with neither myofibroblast transdifferentiation, proliferation nor apoptosis of gingival connective cells in monkeys.